Muslim states and implementation of the Convention on the Rights of the Child: A special reference to Malaysia - Hamid, Abdul Ghafur@Khin Maung Sein (2012)
The Convention on the Rights of the Child (CRC) is the only human rights treaty to which all Muslim States are parties. The main objective of this paper is to look into the difficulties of Muslim States in the implementation of the Convention and a special reference is given to the Malaysian experience. The primary sources of reference are country reports by States parties and concluding observations of the CRC Committee. First of all, the paper takes on the issue of whether Islamic law is a major stumbling block to the implementation of the Convention. The paper argues that as a religion of mercy, Islam is very much concerned about vulnerable people and that despite an unavoidable tension between Islamic law and certain provisions of the CRC, the two are not irreconcilable. The paper then assesses the validity of Malaysia’s reservations to the CRC and concludes with suggestions for changes in the domestic laws and policies of Malaysia to be in compliance with the CRC.